A construção do arranjo institucional da RMBH: entre o autoritarismo e a democracia - Leonardo Bedê Lotti (2023)
The present work focuses on the trajectory of the 50-year formation of the legal-institutional arrangement of the Metropolitan Region of Belo Horizonte (RMBH). This trajectory begins in the authoritarian political period in 1974, goes through the years of democratic transition in the 1980s, and continues into the years of consolidated political democracy post-1988. Over these five decades, three legal-institutional models for RMBH are identified: the first existing in the years 1974-89; the second in the years 1989-2004; and finally, the third from the year 2004 to the present. In order to understand the weave of threads of relationships between ideas, people, circumstances, interests, and chance events that shaped these three legal-institutional models, the work was developed through literature review and the examination of official documents, technical documents, newspapers, proceeding records, and interviews with individuals related to the investigated institutions. Providing a panoramic view of the trajectory of RMBH institutions, the work contributes especially to the understanding of the second legal-institutional model, from 1989 to 2004, considering that there are few academic studies on this subject. Theoretical and methodological support was sought from authors who proposed ideas for the historiography of institutions, such as Jacques Revel and Sarah Feldman. These authors propose epistemologies and criteria for the understanding and delimitation of institutions as historiographical objects, suggesting relevant research approaches.